Immunological and Translational Aspects of NK Cell-Based Antitumor Immunotherapies - Shevtsov, Maxim; Multhoff, Gabriele (Frontiers in Immunology, 2016)
Natural killer (NK) cells play a pivotal role in the first line of defence against cancer. NK cells that are deficient in CD3 and a clonal T cell receptor (TCR) can be subdivided into two major subtypes, CD56dimCD16+ cytotoxic and CD56brightCD16- immunoregulatory NK cells. Cytotoxic NK cells directly kill tumor cells without previous stimulation by cytotoxic effector molecules, such as perforin and granzymes or via death receptor interactions, but also act as regulatory cells for the immune system by secreting cytokines and chemokines. The aim of this review is to highlight therapeutic strategies utilizing autologous and allogenic NK cells, combinations of NK cells with monoclonal antibodies to induce antibody dependent cellular cytotoxicity (ADCC), or immune-checkpoint inhibitors. Additionally, we discuss the use of chimeric-antigen-receptor (CARs) engineered NK cells in cancer immunotherapy.